2009
DOI: 10.1002/jcp.21836
|View full text |Cite
|
Sign up to set email alerts
|

Cell type specific chromosome territory organization in the interphase nucleus of normal and cancer cells

Abstract: Numerous studies indicate that the genome of higher eukaryotes is organized into distinct chromosome territories and that the 3-D arrangement of these territories may be closely connected to genomic function and the global regulation of gene expression. Despite this progress, the degree of non-random arrangement remains unclear and no overall model has been proposed for chromosome territory associations. To address this issue, a re-FISH approach was combined with computational analysis to analysis the pair-wis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(75 citation statements)
references
References 68 publications
5
70
0
Order By: Relevance
“…Marella et al in 2009 [ 40 ], used normal human WI38 lung fi broblast and MCF10A epithelial breast cells and identifi ed that similar levels of association were found in WI38 and MCF10A (both are non-tumorigenic) for chromosomes 1, 4, 11, 12, 14, and 16, whereas a nearly twofold increase in chromosomes 4 and 16 associations was found in a malignant breast cancer cell line (MCFCA1a) compared to the related normal epithelial cell line (MCF10A). This demonstrates that chromosome associations are cell-type specifi c and undergo alterations in cancer cells [ 40 ]. Furthermore, Wiech et al 2005 analyzed chromosome 8 positions in wax embedded pancreatic cancer tissue samples.…”
Section: Alterations To Genome Organization In Cancermentioning
confidence: 97%
“…Marella et al in 2009 [ 40 ], used normal human WI38 lung fi broblast and MCF10A epithelial breast cells and identifi ed that similar levels of association were found in WI38 and MCF10A (both are non-tumorigenic) for chromosomes 1, 4, 11, 12, 14, and 16, whereas a nearly twofold increase in chromosomes 4 and 16 associations was found in a malignant breast cancer cell line (MCFCA1a) compared to the related normal epithelial cell line (MCF10A). This demonstrates that chromosome associations are cell-type specifi c and undergo alterations in cancer cells [ 40 ]. Furthermore, Wiech et al 2005 analyzed chromosome 8 positions in wax embedded pancreatic cancer tissue samples.…”
Section: Alterations To Genome Organization In Cancermentioning
confidence: 97%
“…Hence, the dynamic spatio-temporal organisa t i o nw i t h i ni n t e r p h a s e nuclei, so-called nuclear organisation, correlates with functional status within a "healthy" nucleus and alterations in this organisation are commonly seen when nuclear function is altered or reprogrammed in disease (reviewed in: Dauer and Worman 2009;Lever and Sheer 2010;Misteli 2010;Stein et al 2010;Rajapakse and Groudine 2011). Disease-specific patterns of chromosome territory organisation are especially notable in cancer (Cremer et al 2003;Meaburn and Misteli 2008;Marella et al 2009), laminopathies such as Hutchinson-Gilford Progeria syndrome (Bridger and Kill 2004;M i s t e l i2005; Elcock and Bridger 2010) and X-linked EmeryDreifuss muscular dystrophy (Boyle et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Cremer et al [2003] reported different patterns of CT position for chromosomes 18 and 19 in normal and in tumor cell lines. In a more recent study, Marella et al [2009a] argued for a difference in CT association for chromosomes 4 and 16 in breast cancer lines compared to normal cells. In addition, several studies have highlighted that certain translocations could be generated due to close proximity of the chromosomes involved.…”
Section: Chromosome Territories and Nuclear Organizationmentioning
confidence: 99%